2017
DOI: 10.18632/oncotarget.16710
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced PLOD2 promotes proliferation, migration and invasion via PI3K/Akt signaling in glioma

Abstract: Gliomas are the most common form of malignant primary brain tumors with poor 5-year survival rate. Dysregulation of procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 (PLOD2) was observed in gliomas, but the specific role and molecular mechanism of PLOD2 in glioma have not been reported yet. In this study, PLOD2 was found to be frequently up-regulated in glioma and could serve as an independent prognostic marker to identify patients with poor clinical outcome. Knockdown of PLOD2 inhibited proliferation, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 40 publications
(45 reference statements)
4
74
0
Order By: Relevance
“…Then, the biological functions of P4HA2 was examined. Similar with the findings in breast cancer [20], knockdown of P4HA2 was also found to inhibit glioma proliferation, migration and invasion in vitro and tumor xenograft growth in vivo. However, the underlying molecular mechanism is elusive.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Then, the biological functions of P4HA2 was examined. Similar with the findings in breast cancer [20], knockdown of P4HA2 was also found to inhibit glioma proliferation, migration and invasion in vitro and tumor xenograft growth in vivo. However, the underlying molecular mechanism is elusive.…”
Section: Discussionsupporting
confidence: 84%
“…Among the collagen receptors, the DDRs has been tightly associated with the PI3K/AKT signaling pathway, because of the C-terminal of DDR1 kinase domain contains the YELM binding motif for association with the p85 subunit of PI3K [36]. As previous literature has demonstrated that type I-IV collagens can all combine with DDRs [37,38] and deposited by P4HA2 [6,20] , we think at least the DDRs could theoretically mediate the collagen-dependent regulation of PI3K/AKT signaling pathway by P4HA2 in glioma, though it needs further confirmation. With the downregulation of collagen I, III and VI by P4HA2 silencing in glioma cells, a novel signal axis of P4HA2-collagen-PI3K/AKT pathway is proposed in contribution to glioma progression.…”
Section: Discussionmentioning
confidence: 99%
“…Akt activation promotes cellular growth and survival, and control of migration and invasion activities in GBM has been linked to activation of the PI3K/Akt pathway . We hypothesized that IL‐17A may facilitate PI3K/Akt pathway activation in U251 and U87 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we observed that A549 HxEVs were enriched in the golgi-expressed glycosylation enzyme alpha 6-mannosylglycoprotein 6-beta-N-acetylglucosaminyltransferase B (MGAT5B) which is a critical regulator of cancer cell-cell contact, EMT, and metastasis [32]. Furthermore, the α-ketoglutarate-dependent enzyme PLOD2 can hydroxylate pro-collagen within the ER and has been implicated in hypoxic cancer cell invasion in various experimental models [47][48][49][50][51][52]. Taken together, these data indicate that hypoxia stress stimulates cancer cell protein synthesis and EV distribution to induce diverse functional effects that likely extend beyond local survival strategies.…”
Section: Several Of These Proteins Have Been Reported In Other Contexmentioning
confidence: 99%